100 Greatest Trips: From the Editors of the World's Leading Travel Magazine - Editor Miranda, Jennifer [et al.] (New York Travel + Leisure Books, 2011)
From Travel & Leisure, the world's leading travel magazine, comes the newest edition of 100 Greatest Trips, an invaluable and inspiring compendium of the year's most distinctive destinations. Whether your dream is to escape to a thatched-roof safari camp in the heart of a South African game reserve, explore emerging wine regions in Macedonia, live out your own Roman holiday in an Italian bon vivant's penthouse; or find the best spot to enjoy a kleine Mokka in Vienna, 100 Greatest Trips points the way to the places you'll want to go next. BONUS: useful travel tips; mini-guides to each destination, with maps and recommendations for hotels, cruises, restaurants, boutiques, galleries, museums, and tour operators; and more than three hundred fifty color images from T&L's award-winning photographers.
Include Maps and Colored Illustrations
Keywords: Travel -- Guidebooks